WIND LOAD PREDICTING; HOW COULD CFD REPLACED WIND TUNNEL TEST - Adi Susila, I Gede (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009, 2009)
Computational Fluidal Dynamic (CFD analysis) is highly pointed to solve a number of wind tunnel test problem on the computer simulation. Largeeddy simulation (LES) technique with the Smagorinsky eddy-viscosity model has been applied in order to predict pressure coefficients for 3-D domes and catenoid models. “Fluent” has been used to analyze the flows. Published data of Maher and the ASCE have been used as the basis guideline to enable wind loading to be applied appropriately. Result of LES computations are compared with those from laminar models as well as those from turbulent models based on Reynolds–average Navier- Stokes equation (RANS model) and those from experiment. The numerical experiment results for all models with various configurations to be exited by the turbulent wind forces were identified. The LES results from 3D computational agreed very well with the experimental or published data. For the dome case of h/d=1/2 ratio, the result can be sort it out into the maximum positive Cp=+0.621 and the maximum negative in the centre of dome is Cp = -1.2. The coefficient offered was quite similar to the published data of Cp=+0.6 and Cp=-1.0, respectively. CFD has been shown to a reasonable prediction of wind pressure distributions. It conceivably could replace some wind tunnel tests.
Keywords: wind loads, wind tunnel test, published data, CFD method, LES (Large Eddy Simulation) model.